2015
DOI: 10.1186/s12891-015-0484-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Intraligamentary Stabilization (DIS) for treatment of acute anterior cruciate ligament ruptures: case series experience of the first three years

Abstract: BackgroundIn recent years, the scientific discussion has focused on new strategies to enable a torn anterior cruciate ligament (ACL) to heal into mechanically stable scar tissue. Dynamic intraligamentary stabilization (DIS) was first performed in a pilot study of 10 patients. The purpose of the current study was to evaluate whether DIS would lead to similarly sufficient stability and good clinical function in a larger case series.MethodsAcute ACL ruptures were treated by using an internal stabilizer, combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
162
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(175 citation statements)
references
References 55 publications
6
162
1
6
Order By: Relevance
“…reported outcomes at medium-to long-term follow-up (range of mean follow-up 43.3-79 months) 41,48,49,52 including the mean IKDC subjective score (range 87.3-100), the mean Lysholm score (range 85.3-100), and the mean Tegner activity score (range 5-7). The remaining 10 studies 36,40,[42][43][44][45][46]50,51,53 reported the same outcome measures at short-term follow-up (range of mean follow up 12-38.4 months). At final follow-up, these studies reported a mean IKDC subjective score of 89.5-98, a mean Lysholm score of 93-100, and a mean Tegner activity score of 5-7.…”
Section: Clinical Outcomes Reported In Comparative Studiesmentioning
confidence: 92%
See 4 more Smart Citations
“…reported outcomes at medium-to long-term follow-up (range of mean follow-up 43.3-79 months) 41,48,49,52 including the mean IKDC subjective score (range 87.3-100), the mean Lysholm score (range 85.3-100), and the mean Tegner activity score (range 5-7). The remaining 10 studies 36,40,[42][43][44][45][46]50,51,53 reported the same outcome measures at short-term follow-up (range of mean follow up 12-38.4 months). At final follow-up, these studies reported a mean IKDC subjective score of 89.5-98, a mean Lysholm score of 93-100, and a mean Tegner activity score of 5-7.…”
Section: Clinical Outcomes Reported In Comparative Studiesmentioning
confidence: 92%
“…The remaining 14 studies were Level IV cases series. [40][41][42][43][44][45][46][47][48][49][50][51][52][53] The flowchart for the search strategy is depicted in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations